Integrating Sustainability into Accounting Practices: A Review of Social and Environmental Accounting - Wahyuni, Wahyuni; Sumarni, Sumarni; Fadilah, Nur Fadia; Nurhalizah, Nurhalizah (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores the challenges and opportunities associated with implementing Social and Environmental Accounting (SEA) in Small and Medium Enterprises (SMEs) in emerging markets and the impact of inconsistent global reporting standards on multinational companies. Research Design and Methodology: The research employs a qualitative approach, incorporating a systematic literature review, to analyze existing studies on SEA, with a primary focus on SMEs in emerging markets. The study also examines the role of economic instability and regulatory gaps in shaping SEA practices. Findings and Discussion: The findings reveal that SMEs in emerging markets face significant challenges in implementing SEA due to economic instability, limited resources, and inadequate regulatory support. On the other hand, multinational companies need more harmonized global reporting standards, which complicates the consistency and comparability of sustainability reporting across borders. The study highlights the need for tailored support mechanisms for SMEs and the importance of advocating for global reporting standardization. Implications: The study has two key implications: it contributes to the academic discourse by addressing underexplored areas in SEA research, and it offers practical insights for policymakers and business leaders to enhance the adoption of SEA practices. The study also highlights the importance of establishing consistent sustainability reporting frameworks to foster transparency and accountability in global business practices.